(3OQGSI YdejI h JWHjbjIs - (3aJMj GMeO jMj(B, (3GdYGdes ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3GdJbjjS h GdehGUaGJ , GdLhOI h GOGQI GdLhOI GdTGedI , eHGOF h ebGjjS CfXeI GdLhOI GdYGdjI , GdJWHjb GdYdej dehGUaGJ GdLhOI GdbjGSjI GdOhdjI , GdOdjd GdGQTGOj ddLhOI , GdehGUaGJ GdbjGSjI GdOhdjI dGOGQI GdHjFI eLehYI GdGjRh (B14000(3, dLGf Ch OhGFQ GdLhOI h eJWdHGJ JWHjbgG , GdJObjb Ydi GdLhOI , GdJObjb GdNGQLj h GdMUhd Ydi TgGOGJ GdLhOI h eQGMd GdMUhd Ydi TgGOI GdLhOI (BISO 9000 .s
(3eQGLY U(B.249s
Keywords: (3GdEjRhs; (3GdJbjjSs; (3GdehGUaGJ GdbjGSjIs; (3VHW GdLhOIs